Cobertura de exoesqueleto del camarón (Penaeus Vannamei), como sustituto de la apanadura en la calidad y aceptabilidad del rebozado de camarones apanados - Delgado Macías, María José (2023)
The aim of this research was to evaluate the behavior of shrimp (Penaeus vannamei) exoskeleton coating as a breaded coating on fried shrimp. The main objective was to evaluate the behavior of this coating in terms of physicochemical quality, microbiological viability, texture profile and sensory preference, applying an experimental method where one factor was studied: In addition, the stability of the shrimp exoskeleton coating during storage was evaluated by means of microbiological counts and, finally, the texture (Instrumentation) of the shrimp exoskeleton coating on fried breaded shrimp was evaluated. A DBCA design with a three-level factor and a two-level block was applied, assigning three replicates to each treatment, obtaining 18 experimental units. As a result, all treatments complied with the physicochemical and microbiological parameters of the coating, as well as the texture profile and sensory preference; in terms of physicochemical quality, it was determined that the shrimp exoskeleton coating has a higher amount of proteins and fibers than the conventional coating. In addition, a significant decrease in fat and total carbohydrate content was evidenced in fried shrimp with the exoskeleton coating. In microbiological terms, it was found with the presence of molds and yeasts, but within quality parameters. Regarding the texture profile (instrumental), a result was obtained in the A2T1 treatment (thin coating * simple breading), which presented greater firmness and elasticity; in addition, these shrimps had less moisture loss during the frying process. Finally, as for the sensory preference of the 70 untrained tasters, it was found that consumers prefer the flavor and texture of the treatments A1T1 (floury coating * single breading), and A3T1 (thick coating * single breading), and A3T2 (thick coating * double breading). This shows that the results obtained indicate that shrimp exoskeleton coating can be a viable and healthy alternative to conventional breading in breaded shrimp batter, since it improves their physicochemical quality.